PRINCIPLES AND CONVENTIONS. - Finney, H. A. (The Accounting Review, 1944)
Abstract In recording of transactions and preparation of periodical statements, accountants are supposed to be governed by accounting principles and accountants' certificates which usually include an expression to the effect that the statements have been prepared in accordance with generally accepted accounting principles. And yet there is nowhere a compilation or code of accounting principles. Accountants' reports provide ample evidence that accounting is not controlled by a body of principles which result in uniformity of procedure and treatment. In the first place, many rules and procedures of accounting are not of a fundamental nature. In the second place, principles, principles cannot be established in accounting by experimentation or by authoritative pronouncements. In the third place, it is not desirable that accounting procedures should be reduced to a rigid uniformity by any detailed statement of conventions and rules. Accountancy must meet varying requirements of different businesses operating under differing conditions and must be prepared to adjust itself to changes in the economic system.